Allergic reactions to rubber condoms. Issue 3 (June 1989) - Rademaker, M; Forsyth, A
Abstract : With the increased use of condoms, contact dermatitis to rubber is being seen more often. To develop a rubber condom suitable for use by rubber sensitive people, a "hypoallergenic" condom, which is washed in ammonia to reduce the residues of rubber accelerators, has been manufactured. Fifty patients allergic to various rubber accelerators were patch tested with an ordinary condom and the new washed condom. Fifty patients undergoing routine patch test investigation who were not allergic to rubber were also tested as controls. Twenty two of the rubber sensitive patients had a positive reaction to the new rubber condom compared with four of the control patients. Washing rubber condoms in ammonia does not appear to reduce the residues of rubber accelerators sufficiently for their use by rubber sensitive people. A non-allergenic condom is required.